Spectrum sharing model for OFDMA macro-femtocell networks. (2015) - Estrada, Rebeca; Otrok, Hadi; Dziong, Zbigniew; Barada, Hassan
Enhancing the network throughput while supporting non-uniform user distribution and dense femtocell deployment is a challenge in OFDMA networks. Previous research works focus on spectrum partitioning or spectrum sharing with interference managements regardless the user distribution or mobility. In this paper, we propose a spectrum sharing approach that maximises the network throughput using Linear Programming. Power adaptation is performed to mitigate the interference and to guarantee QoS downlink transmissions. Our solution is able to: 1) fairly allocate resources to each macrocell zone taking into account the user distribution; 2) optimally reuse the bandwidth allocated to inner MC zones inside femtocells located in outer zones; 3) optimally determine the serving base station, subcarriers and transmitted power for downlink transmissions taking into account user locations and demands. Simulations are conducted to show a comparison of our solution with two SP approaches with and without partial bandwidth reuse incorporating user mobility.